The Expansion of a Single Bacteriophage Leads to Bacterial Disturbance in Gut and Reduction of Larval Growth in Musca domestica - Zhang, Xinyu; Wang, Shumin; Zhang, Qian; Zhang, Kexin; Liu, Wenjuan; Zhang, Ruiling; Zhang, Zhong (Frontiers in Immunology, 2022)
The housefly larvae gut microbiota influences larval health and has become an important model to study the ecology and evolution of microbiota–host interactions. However, little is known about the phage community associated with the housefly larval gut, although bacteriophages are the most abundant members of the microbiota and have the potential to shape gut bacterial communities. Changes to bacteriophage composition are associated with disease, but how phages impact insect health remains unclear. We noticed that treating 1-day-old housefly larvae with ~107, ~109, and ~1011 phage particles per ml of bacteriophages led to changes in the growth and development of housefly larvae. Additionally, treating housefly larvae with bacteriophages led to bacterial composition changes in the gut. Changes in the compositions of these gut bacteria are mainly manifested in the increase in harmful bacteria, including Pseudomonas and Providencia and the decrease in beneficial bacteria, including Enterobacter and Klebsiella, after different growth and development periods. The alterations in gut microbiota further influenced the larval growth and development. Collectively, these results indicate that bacteriophages can perturb the intestinal microbiome and impact insect health.